RETRACTED: Effect of Islamic Financial Development on Carbon Emissions: A Spatial Econometric Analysis - Al-Silefanee, Rebean Ramadhan; Mamkhezri, Jamal; Khezri, Mohsen; Karimi, Mohammad Sharif; Khan, Yousaf Ali (Frontiers in Environmental Science, 2022)
In this study, using data including 36 countries in the period 2013 to 2018, the factors affecting CO2 emissions in Islamic countries have been studied, emphasizing the role of Islamic financial development. The results of estimating the spatial econometric method show that there is no spatial relationship between CO2 emissions between the studied countries. The test results confirm the existence of the Environmental Kuznets hypothesis. Besides, trade openness and energy consumption have led to more CO2 emissions. In this study, the effects of conventional financial development variables including financial market and financial institutions variables investigated. The results show that the two variables do not have direct and significant effects on CO2 emissions and only when their nonlinear and spillover effects on energy consumption and economic growth were taken into account, their significant effects on CO2 emissions appear. Also, the development of financial institutions has an inverted U-shaped relationship with carbon emission intensity. Based on the results, the development of financial markets and financial institutions leads to a significant positive increase in CO2 emissions, but the negative coefficient of the interaction between financial development and energy consumption indicates that financial development guarantees energy efficiency, which reduces the intensity of carbon emissions. The results indicate that the growth, expansion, and depth of Islamic finance, such as total assets, asset quality, earnings, and efficiency of Islamic banks can lead to a non-linear increase with a U-shaped relationship with CO2 emissions. Also, the study of the spillover effects shows that in addition to their direct and positive effects on CO2 emissions, the increase of social responsibility in Islam and consumer education and awareness about Islamic Banking Energy efficiency reduces the positive effects of energy consumption on greenhouse gas emissions.